Clinical and electrophysiological correlation in patient with optic neuritis - Chang Arraño, Lianne Alicia; Delgado Suárez, Iván; Querts Méndez, Odalis; Sagaró del Campo, Nelsa (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: Optic neuritis is a disorder frequently find in our environment. Material and methods: A descriptive and traverse study was performed in patients with diagnosis of optic neuritis, that attended to the neurophthalmology service of the ophthalmological center, at the Santiago General Hospital "Dr. Juan Bruno Zayas Alfonso ", from the province of Santiago de Cuba, with less than a week of evolution of the disease, and visual acuity greater than 0.3, cooperatives and without refractive opacities, or neurophthalmologic diseases, during the period from December 2017 to November 2018. Ophthalmological clinical evaluations and electrophysiological studies of visual evoked potentials to pattern reversal, at diagnosis and eight weeks of evolution were carried out. Objective: To identify the relationship possible between the electrophysiological parameters obtained by visual evoked potentials with the ophthalmological clinical evaluation. Results: alterations predominantly of the parameters of latency and duration of the visual evoked potentials, in relation to the impairment of the clinical evaluations explored. Conclusions: The visual evoked potentials are an effective tool in diagnosis, and complement the clinical evaluation of patients with optic neuritis.